Geoelectric Signatures of Palnad Sub Basin and Nallamalai Fold Belt, Cuddapah Basin, India - Konda, Shankar; Patro, Prasanta K.; Rao, C.K. (My University, 2015)
Broadband magnetotelluric investigations were carried out along NW-SE profile from Potuluru to Anjanpalli in the NE part of Cuddapah basin. The 84 km profile is adjacent to the Eastern Ghat Mobile Belt (EGMB) and Eastern Dharwar Craton (EDC), India. Sixteen stations were established with a station interval of 2 to 7 km. The time series data were processed with single site and remote reference approach to derive robust MT transfer functions. Regional strike analyses indicate that the majority of the MT data is consistent with the assumption of a 2-D geo-electric strike direction, which is N40°E. Both transverse electric and transverse magnetic mode data were inverted using 2-D non-linear conjugate gradient algorithm. A conductive (40-300 Ohm.m) zone C1 is identified with 350 m to 2000 m thick sediment representing Palnad sub basin (PSB). The low resistivity could be due to presence of base metals (Cu, Pb, Zn) within the Banaganapalli quartzites and Narji limestone. The two-dimensional geo-electric model derived demarcated a moderately low resistive feature (450 Ωm - 800 Ωm) C2 dipping southeast in the centre of the profile. The moderately conductive nature of C2 could be due to the presence of Palnad sub-basin sediments entrapped along the fault zone. The feature of C2 coincides with Nallamalai Fold Belt (NFB). The dipping resistive crustal layer in the NE parts of Cuddapah basin suggest E-W compression along the eastern margin during the Neoarchaean-Neoproterozoic (~2700 Ma – 970 Ma) tectonic convergence between India and east Antarctica.
Keywords: Cuddapah basin; Palnad sub-basin; Geoelectric signature; Magnetotellutics; 2D inversion